Evaluation of confirmatory data following the Article 12 MRL review for picolinafen - Anastassiadou, Maria (EFSA J, 2018)
The applicant BASF Agro B.V. submitted a request to the competent national authority in Germany to evaluate the confirmatory data that were identified for picolinafen in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new validated analytical method for enforcement of the residue in dry/high starch‐, high water content‐, high acid content‐ and high oil content commodities and a new validated analytical method for enforcement of the residue in ruminant matrices were submitted. The data gaps were considered satisfactorily addressed. The new information provided may require a revision of the existing MRLs for barley, oat, rye and wheat and for products of animal origin. The risk assessment performed for picolinafen was updated. No consumer intake concerns were identified.